Lean UX Research: um framework para pesquisa em design construtivo - Ferreira, Vinícius Afonso Raimundo (Universidade Federal de São Carlos, 2022)
Constructive Design Research (CDR) aims to produce design knowledge through experimentation and debate within the academic community about the process of designing and evaluating an artifact. However, many studies in this area neglect important details when reporting the methodology and procedures used, as well as the context and justifications for the decisions made in both design and evaluation, negatively affecting the contribution of these studies in a theoretical and practical sense. This neglect is due to the lack of structure, clarity, and objectivity of the documentation. In this context, this Ph.D. thesis proposes a framework called Lean UX Research, composed of a process model associated with a set of guidelines that help the production of scientific knowledge through more focused design research with an artifact and a more concise and structured CDR. This framework extends the Lean UX methodology, an iterative process of creating, validating, and reflecting on prototypes to find a solution to complex problems based on agile methods. Thus, the model and guidelines allow researchers to situate themselves in the CDR, selecting the most appropriate methods and tools at each stage. The formalization of this framework involved a broad literature review of design processes and design research, and agile methods applied in design and documentation to be grounded in the theory and state of the art of existing practices. To evaluate the framework, an inspection by experts was carried out, which resulted in its refinement, establishing a methodological framework that supports design and research equally, while avoiding unnecessary documentation. Thus, as a product of better documentation of the design research process, it is possible to build and refine theories, methods, and tools. Furthermore, the adoption of research programs in this framework will allow research to progress in a more linear way, consolidating Design as a discipline and a research practice.
Lean UX Research: a framework for constructive design research
Keywords: Lean UX; Pesquisa em design construtivo; Processo de pesquisa; Constructive design research; Research process; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO